1998
DOI: 10.1007/bf02237063
|View full text |Cite
|
Sign up to set email alerts
|

Rectal washout eliminates exfoliated malignant cells

Abstract: Rectal washout eliminates exfoliated malignant cells in the rectum in the vicinity of the anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 17 publications
1
52
0
7
Order By: Relevance
“…Data from clinical and experimental studies show that irrigation fluid from the rectal stump contains a large number of exfoliated tumour cells 30,31 , which in vitro and in an immunosuppressed animal model have the potential for further growth 32,33 . Other studies have shown that exfoliated tumour cells are regularly found on stapling devices and may be implanted on the staple line 34,35 . However, the rate of local recurrence (in particular anastomotic recurrence) shows no correlation with the detection rate of exfoliated cells so that, under the conditions of local inflammation, the in vivo growth potential of these cells appears to be limited.…”
Section: Discussionmentioning
confidence: 98%
“…Data from clinical and experimental studies show that irrigation fluid from the rectal stump contains a large number of exfoliated tumour cells 30,31 , which in vitro and in an immunosuppressed animal model have the potential for further growth 32,33 . Other studies have shown that exfoliated tumour cells are regularly found on stapling devices and may be implanted on the staple line 34,35 . However, the rate of local recurrence (in particular anastomotic recurrence) shows no correlation with the detection rate of exfoliated cells so that, under the conditions of local inflammation, the in vivo growth potential of these cells appears to be limited.…”
Section: Discussionmentioning
confidence: 98%
“…25 Rectal washout with saline has been shown to reduce the number of cancer cells within the lumen and at the site of the anastomosis. 26,27 The best results, however, come from performing the rectal washout with a hypotonic solution such as water and/or antiseptic. 28,29 To take this evidence further, if the presence of exfoliated cancer cells lying within the peritoneum were a cause of local recurrence, then theoretically, IOPL would be useful to reduce the number of cancer cells and, hence, the future local recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…Various agents, such as mercuric chloride [8], mercury bichloride [9], chlorhexidine-cetrimide, povidone-iodine [10], and normal saline [11] have been proposed for intraluminal irrigation to decrease the incidence of suture-line recurrence. However, it is not clear whether cytocidal agents are effective in preventing suture-line recurrence at an anastomosis [12].…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical studies have revealed that multiple clusters of malignant cells can collect on a circular stapler used to produce an anastomosis when resecting for rectal cancer [11,13,14]. Gertsch et al [13] and Jenner et al [11] reported that cytology revealed malignant cells in centrifuged saline used for washing circular staplers in nine of ten and eight of ten cases of low anterior resection, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation